Hip and knee arthroplasties in military personnel improve unilateral spinal anesthesia combined with unilateral epidural analgesia. (Texas Journal of Medical Science, 2025)
Surgery is often performed on the feet to produce the necessary sensory blockade with minimal effects on the sympathetic nervous system . application of local anesthesia (SA, EA). preferred [133; 105-115 p]. The purpose of unilateral US is to limit the spread of somatic and sympathetic blockade [ 106; 2379-2402- b ] it primarily reduces hemodynamic complications It provides a number of clinical advantages and [53; 298-311-p] our study patients with low cardiac output It is useful for elderly patients with hypodynamic circulatory conditions